Morphometric Analysis of Stingless Bee (Trigona sp.) in The Area of Kawasan Rumah Pangan Lestari (KRPL) Central Lombok - Eliyan Irmasari; Karnan Karnan; Mohammad Liwa Ilhamdi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study aims to determine the morphometric characteristics of the bee Trigona sp. in the Sustainable Food House Area (KRPL) Central Lombok. The research sample consisted of 28 samples of worker bees Trigona sp. taken from 14 colonies in KRPL. The study was conducted in October-November 2020. The morphological characters of each worker bee were observed and 33 morphometric characters were measured. The results of species identification based on morphological and morphometric characters showed that there were two species of Trigona sp. Those in KRPL are Trigona fuscobalteata and Trigona clypearis. The morphological differences that are quite clear between the two species are the structure of the hairbands on the meso scutum, the color of the abdomen, and the color of the wing venation. The color of the abdomen of Trigona fusco balteata is brownish yellow while the color of the abdomen of Trigona clypealis is blackish brown. Wing venation color the structure of the hairbands is more pronounced in Trigona fuscobalteata. Variations in the measured morphometric characteristics can be seen from the standard deviation values. The highest standard deviation values inspecies Trigona fuscobalteatawerehindwing found in length (SDÃÂ±0.26), body length (SDÃÂ±0.23), forewing length of tegula (SDÃÂ±0.19), and forewing length (SD). ÃÂ±0.18). Meanwhile, in the species, Trigona clypealis the highest standard deviation values were found in body length (SDÃÂ±0.20), forewing length of tegula (SDÃÂ±0.15), and forewing length (SDÃÂ±0.27).